2002
DOI: 10.1002/ijc.10463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dna repair gene polymorphisms on BPDE‐DNA adducts in human lymphocytes

Abstract: To determine whether variations in DNA repair genes are related to host DNA damage, we investigated the association between polymorphism in the XPD gene (codon 199, 312, 751) and the XRCC1 gene (codon 194, 399) and the presence of benzo(a)pyrene diolepoxide adducts to lymphocyte DNA (BPDE-DNA) in a group of male patients with incident lung cancer, all current smokers. BPDE-DNA adducts were analyzed by high-resolution gas chromatography-negative ion chemical ionization-mass spectrometry. XPD and XRCC1 genotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
43
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 25 publications
7
43
1
Order By: Relevance
“…Even though devoid of any known enzymatic activity, XRCC1 is thought to act as a scaffold protein, play a coordinating role for consecutive stages of the BER system (Ladiges, 2006), The XRCC1 Arg399Gln polymorphism is located within the XRCC1 BRCA1 carboxyl-terminal domain (BRCT I) and is hypothesized to have functional significance because it is located within a well-conserved region and encodes a nonconservative amino acid change. However, studies examining its relation with markers of DNA damage or DNA repair function have yielded mixed results, with some studies showing a positive relation (Duell et al, 2002;Qu and Morimoto, 2005) and others observing no relation with the variants (Palli et al, 2001;Pastorelli et al, 2002;Tuimala et al, 2002;Hu et al, 2005;Leng et al, 2005;Laantri et al, 2011 ). In present study we found homozygous variants of XRCC1 Arg399Gln had observably associations with NPC risk.…”
Section: Discussionsupporting
confidence: 42%
“…Even though devoid of any known enzymatic activity, XRCC1 is thought to act as a scaffold protein, play a coordinating role for consecutive stages of the BER system (Ladiges, 2006), The XRCC1 Arg399Gln polymorphism is located within the XRCC1 BRCA1 carboxyl-terminal domain (BRCT I) and is hypothesized to have functional significance because it is located within a well-conserved region and encodes a nonconservative amino acid change. However, studies examining its relation with markers of DNA damage or DNA repair function have yielded mixed results, with some studies showing a positive relation (Duell et al, 2002;Qu and Morimoto, 2005) and others observing no relation with the variants (Palli et al, 2001;Pastorelli et al, 2002;Tuimala et al, 2002;Hu et al, 2005;Leng et al, 2005;Laantri et al, 2011 ). In present study we found homozygous variants of XRCC1 Arg399Gln had observably associations with NPC risk.…”
Section: Discussionsupporting
confidence: 42%
“…The presence of the variant Gln 399 allele has been shown to be associated with measurable reduced DNA repair capacity as assessed by the persistence of DNA adducts (4-6), elevated levels of sister chromatid exchanges (5, 7), increased RBC glycophorin A (4), p53 mutations (8), and prolonged cell cycle delay (9). However, Taylor et al (10) reported that whereas BRCT-I is critical for XRCC1-dependent SSBR for maintenance of genetic integrity, the Arg 399 Gln polymorphism in BRCT-I does not have a significant impact on this function and negative findings were also obtained from other individual studies (11)(12)(13). A large number of molecular epidemiologic studies have been conducted to evaluate the role of the Arg 399 Gln polymorphism on cancer risk; however, the results remain conflicting rather than conclusive (6,.…”
Section: Introductionmentioning
confidence: 99%
“…Some laboratory investigations of XRCC1 codon 399 Gln functionality in human cells suggested that this polymorphism is associated with increased levels of DNA damage after exposure to various mutagens (17)(18)(19). Other reports offered conflicting evidence, suggesting that the 399Gln polymorphism has no adverse effect on DNA repair (20)(21)(22). The 194Trp variant protein does not seem to negatively alter the DNA repair capacity of human cells (18,20).…”
Section: Introductionmentioning
confidence: 99%